Pengaruh Pemanfaatan Globe Sebagai Media dalam Pembelajaran IPS Sekolah Dasar - Amanda Ramadhan Firdaus; Yohana R. U. Sianturi; Tin Rustini (Departement of Mathematics Education, 2023)
This study aims to determine whether student achievement can be improved by using a globe in social studies. This research was conducted with a qualitative approach. In analyzing the data, it was carried out using descriptive analysis with the library research method, namely collecting research data on theories related to the problems discussed in this study, the source of the data obtained as a reference to support this research comes from several relevant articles and journals. and in line with research related to the use of globe media in social studies learning in elementary schools. The results showed that the learning achievement of subjects taught with maps and globes was better than those who did not use and globes.